Kultura i dyplomacja kulturalna Unii Europejskiej na przykładzie Programu „Kreatywna Europa”. Analiza politologiczna - Wawrowska, Hanna (Rocznik Integracji Europejskiej, 2015)
The intention of the author of this paper is to present a scientific analysis of the influence of culture and the cultural diplomacy of the European Union on the animation and stimulation of Europe’s integration process, which is in a constant state of perturbation and lack of stability. It examines the problem-related approach to the European Union’s change and development strategy, including the „Europe 2020” strategy for smart, sustainable and inclusive growth, which envisages the implementation of many new communal initiatives and practical solutions introduced by the European Union, including ones that concern both the cultural sector and the creative and audiovisual sector. The European Union, from 2020 onwards, intends to be ready to reach a high level of employment and efficiency, and a higher level of social integration. To enable this, the European Union must ensure attractive framework conditions for innovation and creativity. In that respect, the cultural sector and the creative and audiovisual sector are the source of groundbreaking ideas which may develop into products and services that could contribute to economic growth and job creation, thereby fighting the crisis and social problems. The economic and social crisis in Europe has also been influencing the world of culture. A series of problematic issues associated with the fragmentation of culture and its inventions are identified, including globalisation and digitalisation, underinvestment, inadequate protection of intellectual property and copyright, and insufficient international cultural cooperation.